FAKTOR DETERMINAN AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Zulfa Rosharlianti (Pusat P2M Politeknik Negeri Batam, 2021)
This study aims to determine the description and determinants of audit report lag factors in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The research independent variable is financial distress, investment opportunity and KAP reputation, while the dependent variable is audit report lag. Samples were taken through purposive sampling, in order to obtain a number of 31 companies. Data analysis techniques used multiple linear regression panel data Random Effect Model. The results of this study are that together financial distress, investment opportunity and KAP reputation have a significant effect on audit report lag. Partially, financial distress has no effect on the audit report lag, investment opportunity has no effect on the audit report lag, and the reputation of KAP has no effect on the audit report lag.